Electrical resistivity of porcelain bodies with natural zeolite addition - ARTIR, RECEP (ELSEVIER SCI LTD, 2010)
In this study, the effect of natural zeolite addition on the electrical properties of porcelain bodies was investigated. Clinoptilolite, which is a type of natural zeolite, was added partially or fully in replacement of quartz in selected electro-porcelain compositions. Samples were fired in an electric furnace with a heating rate of 10 degrees C/min at 1200 and 1250 degrees C with a period of 60 min. The electrical resistance measurements of samples were performed at 50, 200, 400 and 600 degrees C. It was shown that the resistivity of samples increased at 50 degrees C temperature after zeolite addition, while it was decreasing after zeolite addition at higher temperatures. At the same time, it was recognized that the resistivity of samples depends on sintering temperature. The activation energy of electrical resistivity of samples was found to be in the range of 0.79-0.87 eV. (C) 2009 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Electrical properties; Porcelain; Silicate; Insulators; Zeolites; MICROSTRUCTURE; CONSTITUTION